Laparoscopic-Guided Ropivacaine Trocar-Site Infiltration Can Improve Post-Operative Pain Control after Laparoscopic Adrenalectomy. (December 2022) - Cavallaro, Giuseppe; Polistena, Andrea; Petramala, Luigi; Gazzanelli, Sergio; Crocetti, Daniele; Iorio, Olga; Iossa, Angelo; Fiori, Enrico; Bracale, Umberto; De Toma, Giorgio; Letizia, Claudio
Background: There is no consensus on pain control in patients undergoing laparoscopy; nowadays, conventional therapy may be improved by transversus abdominis plane block. The aim of this evaluation is to investigate the role of laparoscopic-assisted trocar-site ropivacaine infiltration during adrenalectomy in pain control Methods: This is a retrospective evaluation of a prospectively maintained database including patients undergoing adrenalectomy. Patients were divided into 2 groups: Group A patients received laparoscopic-assisted trocar-site infiltration of 7.5 mg/mL ropivacaine and Group B patients did not receive any infiltration. All patients received a 24-hour infusion of 20 mg morphine; pain was checked at 6, 24, and 48 hours after surgery by Visual Analogue Scale (VAS) score. A rescue analgesia by was given if VAS score was > 4 or on patient request. Results: No differences in operative time, complications, and post-operative stay and no complications related to trocar-site infiltration were found. 6-hour and 48-hour VAS scores were not found to be significantly different between groups, even if a slight decrease in VAS score in Group A was reported. Group A showed significant reduction in VAS score at 24 hours (2.44 +/− .41 vs 3.01 +/− .78, P < .005) and in the number of patients requiring further analgesic drugs administration (40.6% vs 57.8%, P < .005) Conclusions: Laparoscopic-guided trocar-site ropivacaine infiltration can be considered safe and effective in the management of post-operative pain and in the reduction of analgesic need in patients undergoing laparoscopic adrenalectomy. The retrospective nature of the study and the lack of a consistent series of patients require further evaluations.